ChemInform Abstract: Crystal Growth, Structures, Magnetic and Photoluminescent Properties of NaLnGeO4 (Ln: Sm, Eu, Gd, Tb). Issue 34 (26th August 2014) - Yeon, Jeongho; Hardaway, John B.; Sefat, Athena S.; Latshaw, Allison M.; zur Loye, Hans‐Conrad
Abstract Single crystals of the title germanates are grown from a molten NaOH flux using Na2CO3, Ln2O3, and GeO2 as precursors (sealed Ag tubes, 600 °C, 12 h; cooling to 400 °C with a rate of 4 °C/h).